PERHITUNGAN STRUKTUR JEMBATAN TIPE PRECAST PRESTRESS SUNGAI LONG SEMAMU KABUPATEN MALINAU - BARI, EDUARDUS (KURVA S JURNAL MAHASISWA, 2017)
Prestress concrete bridge is one kind of bridge that can be used to connect the mainland edge to further inland, but the effective capabilities of precast prestress bridge span is from 30 meters to 60 meters, so the existence of the bridge of this type encountered in the span - long span.Bridge in Long Semamu River Planned with the type of precast prestress that will be able to accommodate the volume of vehicles and combination of the load acting on the bridge include permanent action, while the action and environmental action.Precast prestress bridge structure calculation using SNI T-02-2005 regulation on loading on the bridge. Overview calculation includes the calculation of the upper structure consisting of poles parapet, sidewalk, tread plate, the vehicles floor, prestress concrete beams and the bottom structure consisting of abutments, pier, wing wall, and foundation.From the calculations, the reinforcement needs of each structural element is varies, from a diameter of 13 mm to 32 mm. For construction of foundation used type of pile with a diameter of 40 cm and depth of 14 m for abutments, and 19 m for pier.